Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films

Chemically grafted graphite nanosheets dispersed in poly(ethylene-glycol) by gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Panda, Kalpataru; Kumar, Niranjan; Melvin, Ambrose A.; Dash, Sitaram; Tyagi, Ashok Kumar (RSC Advances, 2015)
Graphite nanosheets (Gr-NS) dispersed in poly(ethylene-glycol) (PEG200) medium were subjected to various doses of gamma-irradiation. Hydroxyl functional groups present in PEG are chemically grafted through hydrogen bonding with hydroxyl, carbonyl and carboxylic groups of Gr-NS. The grafting process is driven by the generation of active radicals from solvent radiolysis. Chemical grafting was investigated using X-ray photoelectron spectroscopy (XPS) and Fourier transform infra-red (FTIR) spectroscopy. The results of spectroscopic studies revealed reduction in oxygen functionality of PEG-Gr-NS at higher doses of gamma-irradiation. The gamma-irradiation not only bridges the functionalities between PEG and PEG-Gr-NS but edge and basal plane defects in Gr-NS are further reduced as is evident from Raman analysis. The inter-planar sheet distance in Gr-NS is increased due to intercalated chemical grafting with PEG molecules. The chemical grafting between PEG and Gr-NS and reduction in defects enhance the tribological properties with a decrease of 26% and 32% for the friction coefficient and wear, respectively as compared to PEG alone. The lubrication mechanism is mediated through inter-planar weak forces when PEG is chemically grafted with Gr-NS. The electrostatic interaction of PEG with Gr-NS acts as a molecular bridge thus enhancing the sustainability of tribo-stress. Additionally, in the presence of functionalized PEG-Gr-NS tribo-contact conditions, evidence of deposited graphitic tribo-film was observed from micro-Raman spectroscopy inside the steel wear track. This film further enhanced lubrication mediated through low shear strength interlayer graphite sheets and therefore, antiwear properties were synergistically improved.

Facile gamma radiolytic methodology for TiO2-rGO synthesis: effect on photo-catalytic H-2 evolution - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dhara, S.; Dash, Sitaram; Tyagi, A. K. (International Journal of Hydrogen Energy, 2015)
TiO2 (P25) decorated reduced graphene oxide (rGO) is synthesized by gamma-radiolytic technique using water-ethanol solvent medium. Visible light absorpdon was confirmed by UV-Visible spectroscopy. Photoluminescence (PL) study revealed a decline in electron-hole recombination rate signalled by a sharp fall in luminescence of TiO2. Under such scenario, electron transfer from TiO2 conduction band to the conjugated sheet becomes a preferred pathway in the presence of rGO, which is further confirmed by photocurrent measurement. TiO2 -rGO composite with 1 wt. % rGO was found to be the best composition in terms of visible light absorption, while retaining TiO2 crystallinity. Transmission electron microscopy and Raman spectroscopic studies confirmed the coating of rGO sheet with TiO2 nanoparticles. TiO2 -rGO was found to show about 150 times higher photocatalytic H-2 generation under 250 W UV-Visible light irradiation than pristine TiO2. In addition to this, TiO2 -rGO composite shows hydrogen production yield of 35 mu mol/h.g under visible light (lambda = 400 nm) irradiation. Thus gamma-radiolysis can be considered to be a viable technique, which helps in synthesizing photocatalytically active nanocomposite with high H-2 evolution rate. In the light of these interesting aspects, a detail investigation is carried out to study the effect of rGO concentration and illumination time on photocatalytic yield. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: gamma-radiolysis; H-2 production; Photocatalysis; Reduced graphene oxide; TiO2

Effective noncovalent functionalization of poly(ethylene glycol) to reduced graphene oxidenanosheets through gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram; Tyagi, Ashok Kumar (Journal of Physical Chemistry C, 2016)
High-quality reduced graphene oxide (rGO) nanosheets (NSs) were synthesized by the oxidation of graphite followed by hydrazine treatment for the reduction of the oxygen functionalities. gamma-Radiolysis was then used for the functionalization of the rGO-NSs with poly(ethylene glycol) 200 (PEG200). The functionalization resulted in the intercalation of PEG200 molecules in rGO through hydrogen bonding between the hydroxyl groups of rGO and the oxygen atoms of PEG200 molecules. This resulted in an increase in the d spacing of the graphene sheets and a decrease in the defect density of the carbon network in the rGO. The friction coefficient and wear of sliding steel surfaces were reduced by 38% and 55%, respectively, when 0.03 mg mL(-1) PEG200-functionalized rGO dispersed in PEG200 was used. The lubrication properties can be described by bipolar interactions between PEG200 and rGO, leading to effective dispersion. Chemical analysis of wear particles showed decomposition of rGO into nanosized graphite domains, as exhibited by mechanical energy produced in tribo-contact. Moreover, these domains formed effective and stable tribofilms on the steel wear tracks that easily sheared under the action of contact stress. This significantly enhanced the antifriction and antiwear properties, resulting in improved oxidation resistance of PEG200 under the tribo-contact. It was found that, at high rGO concentrations, the lubrication efficiency decreased as a result of graphene-graphene intersheet collisions, producing mechanical energy and chemical defects at contact interfaces.

Molecular-Pillar-supported functionalized reduced graphene-oxide for energy efficient lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram (Advanced Materials Interfaces, 2016)
Molecular-pillar-supported basal plane of reduced graphene oxide (rGO) is fabricated by polymerizing polyaniline (PANI). In the presence of poly(ethylene glycol) (PEG200), the gamma-radiolysis is used for modifying the functionalization and improving the structural symmetry of PANI and PEG grafted rGO (PANI-PEG-g-rGO). The PANI is covalently and noncovalently grafted onto the surface of the graphene sheets. Carboxyl groups of rGO are linked to the nitrogen atoms in the PANI backbone and an accompanying noncovalent interaction between alkyl chains of grafted PANI and hydrooxylated rGO is formed. Raman and Fourier transform infra-red results confirm existence of stretching vibrations of benzenoid and quinonoid rings in PANI-PEG-g-rGO-functionalized composite, indicating grafting between PANI and rGO through pi-pi interaction. Furthermore, PEG-functionalization through hydrogen bonding with rGO is confirmed when hydroxyl group from the rGO combines with oxygen of PEG. X-ray photoelectron spectroscopy reveals significant increase in carbon, while loading PANI network with rGO followed by gamma-irradiation. Antifriction and antiwear properties of graphene nanocomposite are considerably enhanced to 68.4% and 48%, respectively, as compared to pristine PEG. The unique lubrication properties are explained by PEG functionalized molecular PANI-pillar structure across basal plane of rGO.

TiO2 modification by gold (Au) for photocatalytic hydrogen (H-2) production - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, Sitaram; Tyagi, A. K. (Renewable & Sustainable Energy Reviews, 2016)
TiO2 is indeed one of the widely used semiconductors employed for photocatalytic hydrogen production. Most of its photocatalytic activity-is achieved in its crystalline form. However, its photocatalytic activity is limited to ultraviolet region. For making TiO2 visible light active; Au deposition is strongly recommended due to its surface plasmon feature. Au deposition enhances the photocatalytic activity of both crystalline and nanocrystalline TiO2. Efficiency of photocatalytic activity is controlled by shape and size of Au nanoparticle subsequently the synthetic methodology plays an important role. Herein, we furnish a brief description of TiO2-Au nanocomposite synthesis by different methods viz. sol-gel, photodeposition, deposition-precipitation simple reducing method and dispersion method. A discussion on physical properties of the resultant material is also provided. Three different types of mechanism has been described depending on the type of irradiation and form of TiO2 (crystalline and nanocrytalline). A comparative hydrogen production yield is also tabulated to get an idea about the best synthesis methodology and form of TiO2 for efficient photocatalysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gold nanoparticle; Hydrogen generation; Nanocomposite; Photocatalysis; TiO2

Band alignment and charge transfer pathway in three phase anatase-rutile-brookite TiO2 nanotubes: an efficient photocatalyst for water splitting - Preethi, L. K.; Mathews, Tom; Nand, Mangla; Jha, S. N.; Chinnakonda, Gopinath S.; Dash, Sitaram (Applied Catalysis B-Environmental, 2017)
The study reports electrochemical synthesis, phase evolution and hydrogen generation efficiency of anatase, anatase-rutile and anatase-rutile-brookite (ARB) TiO2 nanotubes for the first time. The SEM and TEM micrographs confirm the tubular morphology of the samples. The presence of anatase, rutile and brookite phases in a single nanotube is confirmed from high resolution TEM analysis. The water splitting efficiency of the three systems are studied under one sun illumination. It is observed that the anatase-rutile-brookite TiO2 nanotubes are highly efficient compared to anatase-rutile or anatase TiO2 nanotubes. The hydrogen generated by ARB composites, after four hours of one sun illumination, is found to be nearly twice that of anatase TiO2 nanotubes and 1.6 times that of anatase-rutile TiO2 nanotubes. The results suggest that the ARB in single nanotube having two junction interfaces, highly facilitate interparticle charge transfer compared to single junction anatase-rutile or bare anatase TiO2 nanotubes. From the deconvolution of PL spectra and the synchrotron radiation assisted valence band edge analysis, the band diagram for the anatase-rutile-brookite phase is constructed. The charge separation and its transfer pathway for efficient photo-assisted water splitting are delineated. This opens a new route for the simple synthesis and study of tri-phase TiO2 for efficient photocatalytic water splitting compared to the widely studied two phase TiO2. (C) 2017 Published by Elsevier B.V.
Keywords: Anatase-Rutile-Brookite; Hydrogen generation; nanotubes; Photocatalysis; photoluminescence; Valence band edge